A Comparative Study Between Five Brands of Amoxicillin/clavulanic Acid (625 mg) Tablets Available in Libyan Drug Market - Somaia Elsaedi,; Fatima Melad,; Akasha, Abdulrhman (AlQalam Journal of Medical and Applied Sciences, 2024)
Amoxicillin/clavulanic acid is a combination penicillin-type antibiotic used to treat a wide variety of bacterial infections. However, there are many Amoxicillin- clavulanic Acid brands marketed in Libya, with different quality and prices. The study was aimed to evaluate the quality of five commercial Amoxicillin- clavulanic Acid (625mg) products available in the Libyan market. This study was conducted to assess quality, all products were examined visually for their organoleptic properties, weight uniformity test, friability, hardness, disintegration test, dissolution test and IR were assayed. We carried out a physical comparison of all Amlodipine tablet products and assessed their quality. All the tested five brands were equivalent and complying with the official tests for weight variation, friability, disintegration and Hardness tests according to USP specifications. The friability test between 0.054% to 0.223%. All formulations were disintegrated between 1.57 to 9.04 minutes. Infra-Red (IR) spectroscopic investigations were revealed no any difference between brands and showed identical peaks compared to the reference. All the available brands in local Libyan pharmacies are having, with in the specified quality range and considerably, can be chosen according to good quality and cost, to improve the therapeutic benefit and patient compliance without interchangeability. أموكسيسيلين/حمض الكلافولانيك هو مضاد حيوي مركب من نوع البنسلين يستخدم لعلاج مجموعة واسعة من الالتهابات البكتيرية. ومع ذلك، هناك العديد من العلامات التجارية لحمض أموكسيسيلين- كلافولانيك المسوقة في ليبيا، بجودة وأسعار مختلفة. هدفت الدراسة إلى تقييم جودة خمسة منتجات تجارية من حمض الأموكسيسيلين-الكلافولانيك 625(ملغ) المتوفرة في السوق الليبي. لتقييم الجودة، تم فحص جميع المنتجات بصريًا لمعرفة خصائصها الحسية، وتم اختبار اختبار تجانس الوزن، والتفتيت، والصلابة، واختبار التفكك، واختبار الذوبان، واختبار الأشعة تحت الحمراء. أجرينا مقارنة فيزيائية لجميع منتجات أقراص أملوديبين وقمنا بتقييم جودتها. جميع العلامات التجارية الخمس التي تم اختبارها كانت متكافئة ومتوافقة مع الاختبارات الرسمية لتباين الوزن والصلابة والتفتيت والتفكك والاختبارات وفقًا لمواصفات USP. اختبار القابلية للتفتيت بين 0.54% إلى 0.223%. تم تفكك جميع التركيبات بين 1.57 إلى 9.04. دقيقة. كشفت التحقيقات الطيفية للأشعة تحت الحمراء (IR) عن عدم وجود أي فرق بين العلامات التجارية وأظهرت قمم متطابقة مقارنة بالمرجع. يمكن اختيار جميع العلامات التجارية المتوفرة في الصيدليات الليبية المحلية، ضمن نطاق الجودة المحدد وبشكل كبير، وفقًا للجودة والتكلفة الجيدة، لتحسين الفائدة العلاجية وامتثال المريض دون إمكانية التبديل